(untitled) (Revista Paradigma, 2022)
It deals with the analysis of public safety as a responsibility of all, provided for in article 144 of the Brazilian Constitution of 1988, in light of the theory of fundamental duties and public security policies for risk reduction in society. It assumes that public safety is a duty founded on solidarity, on the demand for proportional conduct and on the promotion of the fundamental right to security, using the concept of fundamental duty. It addresses the theory of risk in contemporary society and points to the responsibility of all as a condition of fostering a more peaceful society, because in many situations state action is not enough to guarantee fundamental rights. It uses the hypothetical-deductive method and adopts the methodological procedures, bibliographical and documentary study. It presents data from the National Secretariat of Public Security and the Brazilian Forum of Public Security on Community Safety Councils in Brazil and on projects implemented by the Private Business Community to work in this area. It concludes that public security as a responsibility of all, provided for in Article 144 of the Brazilian Constitution, is a fundamental relational duty, according to Casalta Nabais classification, since it can bind the citizen to the State, individuals to the community to which they belong, or people to others, through solidarity. It is a duty to promote the right to public safety by proposing, monitoring and evaluating public preventive security policies, with the participation of physical and legal persons, through Community Safety Councils or specific projects of the Private Business Community. Keywords: Fundamental duty. Public policy. Public security. Risk. Solidarity.